Study Of Palm Oil Residue Potential For Electricity Generation In South Sumatra Indonesia - Muhammad Djoni BUstan (Journal of Applied and Engineering Chemistry, 2011)
This study was aimed to asses technical and economic potential of palm oil residue in south Sumatra taking into account availability, present usage, cost involved and other issues to review the state of art of palm oil residue conversion technology and identify suitable technologies for using in South Sumatra and to identify possible biomass electricity generation and carry techno-economical and environmental analysis of the system. The results show that the potential energy that can be extracted from oil palm solid residue in South Sumatera province taking the efficiency of biomass power generation is about 4.4 PJ/year.It can generate electricity up to 308 GWh/year. The waste water generated was about 1 Million meter cube POME/year. This POME can produce 11,058 m3 methane which is equivalent to 0.4 PJ/year and generate electricity as much as 150 GWh /year.Based on the scenario have been analyzed using GIS software shows that the potential area for 15 MW independent power plant constructions have been identified taking into account availability of feedstock and the maximum allowable distances. Analysis of the financial viability of the projects evaluated using RETScreen. The results for independent power plant showed that the project IRR is lower than the discount rate. However, with the implementation of CER for CDM, the project financialanalysis becomes viable. Moreover, other advantages that can be obtained from these projects are the reduction of GHG emission. Overall, the study clearly indicates the high potential for the generation and use of palm oil residue in South Sumatra.Keywords: Palm Oil residue, power plant, CHP, methane capture, RETScreen, GIS Software